Physical characteristics of mithun of north-east India - HELI, T; SAIKIA, S; BORA, N N (The Indian Journal of Animal Sciences, 2013)
A study was conducted on S6 mithuns of either sex at 1, 12, 24, 36 and above 36 months of age undor the prevailing managemental practices in Lower Subansiri and Papum-pare districts of Arunachal Pradesh. The average values of head conformation, viz. head length, width of fore-head, eye to eye space, muzzle circumferences and ear length of male mithuns were greater than those of female mithuns at different age groups. The hom lenglh was not different (p